World film locations Toronto - Ue, Tom (Intellect Books, 2014)
Toronto is a changing city that has been a source of reflection and inspiration to writers and artists whose work focuses on the conditions and prospects of human life. This book explores and reveals the relationship between the city and cinema using a predominately visual approach.